T cell activation and thymic tolerance induction require different adhesion intensities of the CD8 co-receptor - Knobloch, Martina; Schönrich, Günther; Schenkel, Johannes; Hämmerling, Günter J.; Arnold, Bernd (International immunology, 1992)
Activation of mature lymphocytes requires in addition to the TCR contact with the corresponding antigen the binding of the CD8 or CD4 co-receptors to MHC class I or class II proteins respectively. To investigate the contribution of the CD8 - class I interaction to the elimination of autoreactive T cells during negative selection in the thymus we generated two types of transgenic mice. One set expressed a modified Kb molecule which contained a human HLA-A2 α3 domain, thereby missing the binding residues for the murine CD8 molecules. The second set of mice expressed an anti-Kb specific TCR. Both lines were crossed and in the resulting double transgenic mice the development of Kb-reactlve T cells was followed with an anti-clonotyplc antibody. Surprisingly, efficient clonal deletion In the thymus was still observed, although the reduced CD8 - class l adhesion abrogated effector functions in vivo and in vitro. These results imply that even T cells with intermediate affinity for self are negatively selected In the thymus despite the fact that they are not able to react against self antigens in the periphery. Thus a safety window is created which decreases the risk of autoaggression.